Antibodies to neurofilament light as potential biomarkers in multiple sclerosis. Issue 2 (11th November 2021) - Puentes, Fabiola; Benkert, Pascal; Amor, Sandra; Kuhle, Jens; Giovannoni, Gavin
Abstract : Background and objective: The concentration of neurofilament light (NfL) protein in cerebrospinal fluid (CSF) and blood is widely considered as a quantitative measure of neuro-axonal injury. Immune reactivity to NfL released into extracellular fluids induces specific autoantibody response. We investigated the levels and avidity of antibodies to NfL in patients with multiple sclerosis (MS) treated with disease-modifying therapies (DMTs) and their correlation with disease worsening and NfL protein concentration. Methods: We conducted a prospective longitudinal study in 246 patients with MS (125 DMT-treated and 121 untreated at baseline). Serum levels of NfL antibodies, antibody avidity and immune complexes were determined by ELISA. NfL protein was measured using the Simoa platform. Clinical variables were tested for their association with the measured parameters in multivariate generalised estimating equation models. Results: Multivariate analysis showed that levels of NfL antibodies were higher in progressive MS compared with clinically isolated syndrome (CIS)/relapsing remitting multiple sclerosis (RRMS) (p=0.010). Anti-NfL levels drop with increasing disability score (Expanded Disability Status Scale (EDSS)) (p=0.002), although conversely, were significantly elevated in CIS/RRMS after a recent EDSS increase (p=0.012). Patients receiving DMTs showed decreased levels of anti-NfL (p=0.008), high-avidity antibodies (p=0.017) and immune-complexes compared with untreated CIS/RRMS. Patients with MS switching to natalizumab showed lower levels of anti-NfL but higher immune complexes compared with healthy controls (p=0.0071). A weak association was observed between the levels of NfL protein and NfL antibodies. Conclusions: These results support the potential usefulness of quantifying antibody response to NfL as potential markers of progression and treatment response in MS and need to be considered when interpreting peripheral blood NfL levels.